Mental Health and Migration in Mesoamerica: a Systematic Review: Salud Mental y Migración en Mesoamérica: una revisión sistemática - Torales, Julio; Barrios, Iván; González, Israel (Medicina Clínica y Social, 2018)
Introduction: Millions of people live outside their country of origin, they are immigrants, refugees or exiled, each with their own history, their strengths and weaknesses; but they all have something in common: the fact that they must adapt culturally to the place where they now live, and they must be socially accepted in this new group.  Objective: The main goal of this article was to perform a search and systematic review in order to find research in the fields of mental health and migration, providing a global view of the situation in Mesoamerica and showing the risk factors and the protective factors that influence the migratory process. Methodology: We performed a systematic review of the following databases: PubMed/MEDLINE and LILACS. We included publications from the last five years (2012 – 2017), in English and Spanish, if they were published in indexed journals and if the full text version was available. Results: We found that the most frequent mental disorders were related to stress, the distress generated by the separation from family members, the problems faced when crossing the border, and the conditions that motivate the migration. The most common diagnoses where generalized anxiety disorder, major depressive disorder, post-traumatic stress disorder, and substance use disorder. Conclusions: In Mesoamerica, there is a dearth of research exposing with clarity the current situation of migration and mental health and describing the details of the reality in each country. This is important because, besides from the personal features and support networks that these people have, a fundamental factor that determines their mental health in their new country is the country of origin: the living conditions in this country and the motives that force people to migrate.Keywords: Psychological distress; Migrants; Migratory process; Mental health; Mental disorders.RESUMENIntroducción: Millones de personas viven fuera de su país de origen, son inmigrantes, refugiados o exiliados, cada uno con su propia historia, sus fortalezas y debilidades; pero todos tienen algo en común: el hecho que deben adaptarse culturalmente al lugar donde residen y, por supuesto, ser aceptados en este nuevo grupo. Metodología: Se realizó una revisión sistemática en las bases de datos PubMed/MEDLINE, LILACS. Se incluyeron las publicaciones de los últimos cinco años (2012-2017), en español e inglés, disponibles a texto completo y de revistas arbitradas. Resultados: Se encontró que los trastornos mentales más comunes están relacionados con el estrés, la angustia generada por la separación de los familiares, los problemas que enfrentan al cruzar la frontera y las condiciones que motivan la migración. Se destacan los diagnósticos de trastorno de ansiedad generalizada, trastorno depresivo mayor, trastorno de estrés postraumático, uso y abuso de sustancias. Conclusiones: Existe poca investigación en Mesoamérica que exponga claramente la situación actual de la migración y la salud mental y detalle la realidad de cada país. Lo anterior es importante puesto que, además de las características personales y la red de apoyo con que cuenten estas personas, un determinante fundamental lo constituye el país de origen, la realidad que se vive allí y cuáles son los motivos que obligan a las personas a migrar.Palabras clave: Malestar psicológico; Migrantes, Proceso migratorio; Salud mental; Trastornos mentales.
Keywords: Psychological distress; Migrants; Migratory process; Mental health; Mental disorders